ANALISIS PENGELOLAAN KEUANGAN DESA BERDASARKAN PERMENDAGRI NOMOR 20 TAHUN 2018 (STUDI KASUS DI DESA BALE KECAMATAN GALELA SELATAN KABUPATEN HALMAHERA UTARA) - Aba, Agustinus; Manoma, Suharli (Servqual: Jurnal Ilmu Manajemen, 2023)
Village financial management is an activity that manages village finances better. Good village financial management is based on existing regulations and depends on the ability of the human resources who manage it. The aim of this research is to analyze village financial management activities in Bale Village which include administration, reporting and accountability activities using qualitative descriptive research methods. The research results show the reasons for not using Permendagri No. 20 of 2018 concerning Village Financial Management, namely the lack of understanding by human resources regarding existing regulations. Overall, village financial administration activities in Bale Village are good. Village financial reporting activities in Bale Village are good but there are still discrepancies in reporting to the regions. And village financial accountability activities in Bale Village show that there are still several things that are not appropriate and there is no direct accountability to the community. The village financial management system in Bale Village already uses the Village Financial System (SISKEUDES). It is recommended that the following village financial management activities use Permendagri No. 20 of 2014 concerning Village Financial Management.